2011
DOI: 10.1309/ajcps6c8evycqnrm
|View full text |Cite
|
Sign up to set email alerts
|

Association of JAK2 Mutation Status and Cytogenetic Abnormalities in Myeloproliferative Neoplasms and Myelodysplastic/Myeloproliferative Neoplasms

Abstract: Myeloproliferative neoplasms and myelodysplastic/myeloproliferative neoplasms are heterogeneous disorders. JAK2 mutation testing and karyotyping are routinely used for diagnosis but have not been incorporated into risk stratification in Philadelphia chromosome-negative myeloproliferative neoplasms. This study correlated cytogenetic abnormalities with disease stage and JAK2 status. A total of 179 cases were analyzed for the JAK2 mutation. Among them, cytogenetic data were available for 97 cases-45 of 106 JAK2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…1 It has been proposed that DNA mutations accumulate during the life of an individual as a consequence of failure to correct errors introduced in the genome during the cell replicative process, leading to either activation of oncogenes or silencing of tumour suppressors that operate as driving factors in the initiation of the disease. 2, 3 Indeed, links have been established between age-related MPNs and specific cytogenetic abnormalities, 4 and older patients with MPN exhibit a higher frequency of chromosomal defects. 5 …”
Section: Introductionmentioning
confidence: 99%
“…1 It has been proposed that DNA mutations accumulate during the life of an individual as a consequence of failure to correct errors introduced in the genome during the cell replicative process, leading to either activation of oncogenes or silencing of tumour suppressors that operate as driving factors in the initiation of the disease. 2, 3 Indeed, links have been established between age-related MPNs and specific cytogenetic abnormalities, 4 and older patients with MPN exhibit a higher frequency of chromosomal defects. 5 …”
Section: Introductionmentioning
confidence: 99%
“…A cytogenetic review of 97 cases revealed a higher frequency of cytogenetic anomalies in MPN patients who were positive for JAK2 mutations as compared to those who were negative (51% vs . 27%) .…”
Section: Discussionmentioning
confidence: 97%
“…Cytogenetic abnormalities are routinely assessed in MPN patients to establish a diagnosis but not to stratify disease prognosis, and they are not used for risk stratification as in the case of acute myeloid leukemia . The frequency of cytogenetic abnormalities in MPN varies between 3% and 40% depending on the number of patients at different stages of MPN and MDS/MPN that are included in the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations